Synthesis of Homochiral N‐Heterocyclic Carbene‐Based Nanosheets for Enhanced Asymmetric Catalysis - Xinchao Wang; Zhiwen Wang; Zhaoxing Wang; Tian‐Fu Liu; Shangda Li; Fei Wang; Jian Zhang (Advanced Science)
Abstract Utilizing ultrathin 2D metal–organic framework nanosheets (2D MONs) as supports for incorporating chiral catalysts represents a highly promising avenue in the field of asymmetric catalysis. In this study, four pairs of isostructural chiral metal–organic layers (MOLs) adorned with N‐Heterocyclic carbene (NHC) groups are successfully synthesized. Notably, the obtained bulky (S)‐1‐Zn crystals can be readily delaminated into ultrathin MONs consisting of 1–2 layers through an ion intercalation‐assisted exfoliation process. Subsequent asymmetric catalysis studies revealed that the NHC sites can be effectively activated by a proton sponge while maintaining structural integrity for the subsequent benzoin condensation. Due to their well‐exposed catalytic sites, ultrathin morphology, and porous structure, the (S)‐1‐Zn nanosheets exhibited significantly enhanced yield and enantioselectivity compared to their bulk counterparts and organic precursors. This research highlights an efficient strategy for incorporating chiral NHC species onto 2D MONs, thereby unlocking their immense potential for heterogeneous asymmetric catalysis.